Brief version of the Life Skills Test in Mexican adolescents and young adults in school - Santana-Campas, Marco Antonio (2024)
Life skills are considered necessary to achieve healthy human development and their teaching has spread globally through the implementation of prevention programs in school environments. However, these programs require easy to use instruments with adequate psychometric properties. This study aims to provide validity evidence based on the internal structure for the Life Skills Test, and to design a short version to assess life skills in Mexican adolescents and young people in school. In this psychometric study the Life Skills Test was administered to 897 students (Mage = 20.70, SD = 3.73); 74.7 % were women (M age = 20.49, SD = 3.16), 25.3 % men (M age = 21.33; SD = 5.01). 2.6 % were secondary and upper secondary education, 95.4 % undergraduate and 2% postgraduate students. The original test consists of 80 items and identifies ten life skills. In this research, the original test did not show acceptable fit indices, except for the GFI (.97) and the RMSEA (.073); the proposed brief version, with 40 items, showed validity evidence based on the internal structure, in terms of fit indices obtained with confirmatory factor analysis, invariance analysis and reliability coefficients. Therefore, the brief version is appropriate for use in Mexican adolescents and young people.